Congenital malformations in twins in England and Wales. Issue 1 (March 1991) - Doyle, P E; Beral, V; Botting, B; Wale, C J
Abstract : STUDY OBJECTIVE–The aim was to compare congenital malformation rates in twin births with those in singleton births. DESIGN–The study was an analysis of malformation rates in singleton and twin births using data from the Office of Population Censuses and Survey's Congenital Malformation Notification Scheme. SETTING–This was a national survey of births in England and Wales in 1979-1980 and 1982-1985. PARTICIPANTS–The data comprised 95, 510 reported malformations in 3.7 million singleton births, and 1925 reported malformations in 76, 000 twin births. MEASUREMENTS AND MAIN RESULTS–Twin malformation ratios were calculated using maternal age specific singleton rates as standard. In comparison with singleton births, twins have significantly higher reported frequencies of indeterminate sex and pseudohermaphroditism; anencephaly; patent ductus arteriosis; exomphalos; hydrocephalus; anomalies of the umbilical vessels; atresia or stenosis of the large intestine or anus; and tracheo-oesophageal fistula, atresia or stenosis. Twins also have significant reported deficits of polydactyly and syndactyly; congenital dislocation of the hip; anomalies of the tongue, branchial cleft and auricular sinus; post-anal dimple; and Down's syndrome. CONCLUSIONS–Several major malformations were significantly more common in twins than in singletons. The excess of indeterminate sex and pseudohermaphroditism has not been described before and may be analogous to freemartinism in cattle. Most of the conditions less common in twins are minor, and the reported deficits may be due to underascertainment of the less serious conditions in twins. Down's syndrome is an exception, and the deficit may well be real.